Au(i) N-heterocyclic carbenes from bis-imidazolium amphiphiles: synthesis, cytotoxicity and incorporation onto gold nanoparticles. Issue 3 (4th January 2016) - Rodrigues, M.; Russo, L.; Aguiló, E.; Rodríguez, L.; Ott, I.; Pérez-García, L.
Abstract : Bis-imidazolium amphiphiles capable of forming Au(i ) N-heterocyclic carbenes and gold nanoparticles for potential cancer therapy. Abstract : A gold(i ) N-heterocyclic carbene4 from a bis-imidazolium-amphiphile was synthesized and characterized. The cytotoxicity against HT-29 colon carcinoma and MDA-MB-231 breast adenocarcinoma cells was assessed for the NHC complex4, the imidazolium salt precursor2, and its methyl analogue3, indicating that compounds2–4 are promising cytotoxic agents. Furthermore, the ability of these compounds to be associated with gold nanoparticles was also explored, in order to develop an anticancer drug delivery system. The free ligands displayed more activity when compared with the ligands immobilized on the gold nanoparticles. The synthesized gold particles incorporating the bis-imidazolium salts either2 or3 showed monodisperse spherical shape with sizes of approximately 5 nm.